Neuroprotective peptides fused to arginine-rich cell penetrating peptides: Neuroprotective mechanism likely mediated by peptide endocytic properties - Meloni, B.; Milani, D.; Edwards, A.; Anderton, R.; O'Hare Doig, R.; Fitzgerald, Melinda; Knuckey, N. (2015)
Several recent studies have demonstrated that TAT and other arginine-rich cell penetrating peptides (CPPs) have intrinsic neuroprotective properties in their own right. Examples, we have demonstrated that in addition to TAT, poly-arginine peptides (R8 to R18; containing 8–18 arginine residues) as well as some other arginine-rich peptides are neuroprotective in vitro (in neurons exposed to glutamic acid excitotoxicity and oxygen glucose deprivation) and in the case of R9 in vivo (after permanent middle cerebral artery occlusion in the rat). Based on several lines of evidence, we propose that this neuroprotection is related to the peptide's endocytosis-inducing properties, with peptide charge and arginine residues being critical factors. Specifically, we propose that during peptide endocytosis neuronal cell surface structures such as ion channels and transporters are internalised, thereby reducing calcium influx associated with excitotoxicity and other receptor-mediated neurodamaging signalling pathways. We also hypothesise that a peptide cargo can act synergistically with TAT and other arginine-rich CPPs due to potentiation of the CPPs endocytic traits rather than by the cargo-peptide acting directly on its supposedly intended intracellular target. In this review, we systematically consider a number of studies that have used CPPs to deliver neuroprotective peptides to the central nervous system (CNS) following stroke and other neurological disorders. Consequently, we critically review evidence that supports our hypothesis that neuroprotection is mediated by carrier peptide endocytosis. In conclusion, we believe that there are strong grounds to regard arginine-rich peptides as a new class of neuroprotective molecules for the treatment of a range of neurological disorders.